2023
DOI: 10.3390/agronomy13071854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil-Applied Humic Ameliorative Amendment on the Ligno-Cellulose Quality and Calorific Value of Switchgrass Panicum virgatum L.

Abstract: The main objective of the paper was to determine the ligno-cellulose quality and calorific value of switchgrass Panicum virgatum L. The impact of nutrition treatments (pre-sowing soil humic amendment HA and/or NPK, with annual dose of N on both the treatments, and untreated control UC) and years were evaluated as main effects within a pilot experiment with seven cultivars tested during 2018–2022. Two data sets of acid detergent fiber (ADF), acid detergent lignin (ADL), crude cellulose (CE), hemicellulose (HEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Saidimoradi et al also found that HA mitigated the reduction in relative water content, membrane stability index, chlorophyll content, total biomass, and yield of strawberry to resist salt stress [24]. However, as a pasture plant with certain salt tolerance, previous studies have confirmed that HA promotes the germination, rooting and lignocellulose quality of switchgrass [25,26]. The response of physiological and biochemical indexes of switchgrass such as photosynthetic metabolism and plant growth to HA under salt stress remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Saidimoradi et al also found that HA mitigated the reduction in relative water content, membrane stability index, chlorophyll content, total biomass, and yield of strawberry to resist salt stress [24]. However, as a pasture plant with certain salt tolerance, previous studies have confirmed that HA promotes the germination, rooting and lignocellulose quality of switchgrass [25,26]. The response of physiological and biochemical indexes of switchgrass such as photosynthetic metabolism and plant growth to HA under salt stress remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The quality parameters of acid detergent fiber, acid detergent lignin, crude cellulose, hemicellulose, neutral detergent fiber, and high heating values were evaluated. The results indicated that the cultivar, followed by the year and the nutrition, had the greatest effects on the quality factors studied [18].…”
mentioning
confidence: 95%